2010
DOI: 10.1111/j.1365-2745.2010.01649.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of acorn woodpecker social behaviour on transport of coast live oak (Quercus agrifolia) acorns in a southern California oak savanna

Abstract: Summary1. Many plant species depend upon animals for seed dispersal, yet animals disperse seeds in pursuit of their own social and behavioural agendas. Animal social behaviour affects where and how they forage, so it must also shape patterns of seed dispersal. 2. At Sedgwick Reserve, California, USA, we established a study population of Quercus agrifolia to determine patterns of acorn foraging by the acorn woodpecker (Melanerpes formicivorous). This cooperative breeder lives in social groups that defend territ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(48 citation statements)
references
References 57 publications
3
45
0
Order By: Relevance
“…Woodpeckers can fly kilometers on any given day, but our analyses showed that the effective number of maternal trees found in any single granary (each containing the combined collection from a single woodpecker family's efforts) is 2–3 local trees (Scofield et al. ; Scofield et al. ), as would be predicted by optimal foraging theory (Thompson et al.…”
Section: Contemporary Gene Flow In Trees At a Landscape Scalementioning
confidence: 68%
“…Woodpeckers can fly kilometers on any given day, but our analyses showed that the effective number of maternal trees found in any single granary (each containing the combined collection from a single woodpecker family's efforts) is 2–3 local trees (Scofield et al. ; Scofield et al. ), as would be predicted by optimal foraging theory (Thompson et al.…”
Section: Contemporary Gene Flow In Trees At a Landscape Scalementioning
confidence: 68%
“…For instance, parentage analysis has shown that seeds dispersed beneath a conspecific canopy need not be from that specific mother tree (Godoy & Jordano, 2001) and that the adult plant nearest to the seedling is rarely the parent (Hardesty et al, 2006;Sezen, Chazdon & Holsinger, 2009). Although some of the reviewed studies went beyond reporting distance metrics and acknowledged the fact that seed movement is anisotropic and non-random (SantamarĂ­a et al, 2007;Scofield, Sork & Smouse, 2010), few evaluated the factors that underlie spatial variance in seed dispersal (Russo et al, 2006). Although some of the reviewed studies went beyond reporting distance metrics and acknowledged the fact that seed movement is anisotropic and non-random (SantamarĂ­a et al, 2007;Scofield, Sork & Smouse, 2010), few evaluated the factors that underlie spatial variance in seed dispersal (Russo et al, 2006).…”
Section: (3) Characterizing the Seed Shadowmentioning
confidence: 99%
“…Unlike umbrellabirds, acorn woodpeckers live in highly territorial social groups and tend to forage in the trees proximal to their storage sites, with each territorial group gathering acorns from non-overlapping territories and hence from different trees (Grivet et al, 2005;Scofield et al, 2010Scofield et al, , 2011). However, because lek-breeding among frugivorous bird species is essentially absent from the temperate zone, we must limit our comparisons to species that exhibit other mating systems.…”
Section: Comparisons With Other Lekking and Non-lekking Speciesmentioning
confidence: 99%